2017
DOI: 10.1002/2017rs006392
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Static JPEG Images and RGB Video Frames by Means of Nonlinear Filtering in Conditions of Gaussian and Non‐Gaussian Noise

Abstract: The use of nonlinear Markov process filtering makes it possible to restore both video stream frames and static photos at the stage of preprocessing. The present paper reflects the results of research in comparison of these types image filtering quality by means of special algorithm when Gaussian or non‐Gaussian noises acting. Examples of filter operation at different values of signal‐to‐noise ratio are presented. A comparative analysis has been performed, and the best filtered kind of noise has been defined. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(Yu et al, ) The results of research in comparison of some types image filtering quality by utilizing special algorithm when Gaussian or non‐Gaussian noises acting has been analyzed, and it has been shown that the quality of developed algorithm is much better than quality of adaptive one for RGB signal filtering at the same a priori information about the signal. (Sokolov & Abdullin, ) A channel estimation method based on Kalman filter with STBC codes for multiple‐input multiple‐output (MIMO) systems has been proposed to remove noise on 4G communication channel. (Padmaja & Malleswari, ) A method based on independent component analysis (ICA) has been presented to deal with contaminated ECG signal.…”
Section: Introductionmentioning
confidence: 99%
“…(Yu et al, ) The results of research in comparison of some types image filtering quality by utilizing special algorithm when Gaussian or non‐Gaussian noises acting has been analyzed, and it has been shown that the quality of developed algorithm is much better than quality of adaptive one for RGB signal filtering at the same a priori information about the signal. (Sokolov & Abdullin, ) A channel estimation method based on Kalman filter with STBC codes for multiple‐input multiple‐output (MIMO) systems has been proposed to remove noise on 4G communication channel. (Padmaja & Malleswari, ) A method based on independent component analysis (ICA) has been presented to deal with contaminated ECG signal.…”
Section: Introductionmentioning
confidence: 99%